Impact of Social Media Involvement on Brand Co-Creation during the COVID-19 Outbreak in the Tourism Industry - Raouf, A. R.; Khan, I.; Bilro, R.G.; Cain, L. (Brand Co-Creation Tourism Research: Contemporary issues and Challenges, 2023)
Using Protection Motivation Theory and Service-Dominant Logic, this research develops a model that explores the relationships between perceived risk, fear of COVID-19 (FCV), social media involvement (SMI), brand co-creation (BCO), customer brand engagement (CBE), and revisit intention in tourism industry during COVID19 pandemic. First, results suggest that social media involvement positively impacts tourism-CBE. Secondly, results revealed that CBE’s significant positive effect on BCO and tourist’s revisit intent. Findings also revealed a negative moderating effect of FCV in proposed associations. Fourth, findings showed the social media’s and perceived risk’s indirect impact on co-creation and revisit intent, as mediated via CBE. The model has been tested adopting PLS-SEM, and the empirical results can contribute to the advancement of SMI, CBE, BCO, and revisit intention in tourism-destination services. This study offers key implications for tourist destinations to construct recovery tactics in surviving during outbreak/pandemic to restore tourism.